Strategic innovation, customer relationship management and the performance of SMEs' in Yemen: the moderating role of intellectual capital - Alqershi, Nagwan Abdulwahab Mohammed (2019)
The current study is the culmination of a number of years of research in the field of intellectual capital (IC), strategic innovation (SI) and customer relationship management (CRM) in relation to the pursuit of high performance in small and medium enterprises (SMEs). Against the background of the general theme, there is critical discussion of the performance of manufacturing SMEs in developing countries, in both theory and practice. This synthesis has led to a deeper understanding of the whole topic. Specifically, the current study fills the existing gaps in theory and practice by investigating the nature of the relationship between CRM, SI and SMEs' performance in the manufacturing industry of Yemen. It examines the moderating effects of IC on the relationship between CRM and SI and SME performance. A study relating IC and SI, CRM and SMEs' performance was designed. The survey method was used to collect data from 284 SMEs in the manufacturing industry of Yemen. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used to test the study's hypotheses. Results indicate that only three dimensions of CRM have a significant effect on SMEs' performance. SI has a significant effect on performance. The moderating effects of IC dimensions on the relationship between CRM dimensions and SI and SMEs' performance were examined. Results indicate that IC moderates the relationship between SI and finn performance; it also moderates the relationship between two CRM dimensions, technology based CRM (TCM) and CRM organization (CRMO) but not that between key customer focus (KCF) and CRM know ledge management (KM) and SME performance. The findings of this study offer important insights for owners and managers of SMEs, researchers and policymakers to further understand the effects of SI, IC and CRM on SMEs' performance. SMEs should also be encouraged to develop their CRM, SI and IC to improve their performance.